Dying is a Transition. (May 2013) - Renz, Monika; Mao, Miriam Schuett; Bueche, Daniel; Cerny, Thomas; Strasser, Florian
Purpose: End-of-life care is designed as response to patients' verbally communicated needs. The concept of dying as a process would allow us to improve care. This concept may combine the needs of the dying, their outburst of emotions, gradual maturation, family processes, acute problems such as decreasing independence, with their inner experience and transformation of perception. In this study we explored dying patients' mode of perception, and deeper reasons for anxiety and existential suffering. Methods: Dying inpatients of a major cancer centre treated by an interdisciplinary team were eligible. Psychotherapy records of cancer patients (course, reactions, discussions with nurses and physicians) provided the data. Participant observation and Interpretative Phenomenological Analysis (IPA) was applied. Results: Our data (pilot study N=80/follow-up-study N=600) suggest that patients undergo transition into another state of consciousness beyond anxiety, ego, and pain. Transition appears to have three stages. Anxiety, struggle, denial/acceptance, family processes, and maturation (ie, finding meaning and dignity, coping with trauma) may depend on the transitional process and also hinder or facilitate this transitional process. Conclusions: Understanding dying as transition may induce a radical reinterpretation of what patients need.